If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 4y = 3z + -4 Reorder the terms: 3x + 4y = -4 + 3z Solving 3x + 4y = -4 + 3z Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4y' to each side of the equation. 3x + 4y + -4y = -4 + -4y + 3z Combine like terms: 4y + -4y = 0 3x + 0 = -4 + -4y + 3z 3x = -4 + -4y + 3z Divide each side by '3'. x = -1.333333333 + -1.333333333y + z Simplifying x = -1.333333333 + -1.333333333y + z
| -6g-(-3)g+2g=12 | | 6-12x+4x=30 | | 8a^2-2a=2a(4a-1) | | 3.2=-1k+3.2 | | 7(3e-2f+4)+6e-2= | | -20m-(-15)m+6m=-14 | | 4n+9=10n-12 | | 10x-(3-x)=52 | | 8a^2-2a= | | 17(s-5)=42 | | 20w=5 | | -13x+13x+10x-8x+-x=20 | | -5z+32=-8 | | x^2+10x-999=0 | | b^2-14b+40=-8 | | b^2-14b+40=-8 | | b^2-14b+40=-8 | | -5z+32=-8 | | -5z+32=-8 | | -5z+32=-8 | | 2.25x=x+12.73 | | 6t+15-12=24t-60 | | 6(3x-0.2)=3x-1.2 | | 2.25x=x+12.73 | | 5m-3(5-8)=-14 | | I-3nl-2=4 | | 154+31=61 | | 3m+1.2m=4.2 | | 1=9-4/5(y-15) | | f(x)=30+4x | | -4y-9=19 | | 6y^2(4y^3-5)= |